Non-State Actor Resilience in Strengthening Food Security Governance Networks - Novayanti Sopia Rukmana S; Febrianto Syam; Nani Harlinda; Kittisak Wongmahesak; Saddam Husain Thamrin (Universitas Merdeka Malang, 2026)
Food security governance in Indonesia remains predominantly state-centered, leaving limited space for non-state actors such as Community-Based Organizations (CBOs) and Non-Governmental Organizations (NGOs) to participate meaningfully in the policy process. This study examines the contribution and resilience of non-state actors in strengthening food security governance networks in a regency characterized by high agricultural potential yet persistent food security challenges. Employing a descriptive qualitative approach within an interpretivist paradigm, informants were selected through purposive sampling based on direct involvement in food security policy implementation. They comprised representatives from the local food security agency, CBOs engaged in community-level food programs, and NGOs focused on food issues and community empowerment. Data were collected through semi-structured in-depth interviews, participatory observation, and document analysis, then examined using thematic analysis encompassing data reduction, actor categorization, and contribution mapping within a governance network framework. The findings reveal that non-state actors demonstrate high adaptive capacity through local initiatives including home garden utilization, traditional agriculture revitalization, and food diversification. However, their involvement remains sporadic and confined to the implementation stage. Structural barriers, notably inadequate incentives, weak coordination mechanisms, and limited deliberative space, prevent their strategic engagement in policymaking. This study contributes to the governance network literature by foregrounding the resilience of non-state actors and its implications for participatory food security governance. It argues for a transformation from symbolic participation toward substantive involvement across all policy stages, supported by institutional reforms and incentive schemes that strengthen collaborative governance in decentralized settings.